Game-based learning: Strengthening Islamic Religious Education learning process - Saskiah, S. (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
A pleasant situation in the learning process is one of the things that must be considered in the implementation of the learning process, including in Islamic Religious Education subjects. The implementation of Islamic Religious Education learning at SDN 2 Cantigi Kulon has been running smoothly but is still experiencing deficiencies in terms of student involvement. Therefore, efforts need to be made by teachers to increase student involvement. One effort that can be made is to use the game-based learning method, or game-based learning carried out through the smart snakes and ladders game, so that students are more enthusiastic and active in participating in the learning process. This article aims to describe the form of reinforcement carried out in Islamic Religious Education subjects wrapped in educational games using Islamic smart snakes and ladders games. This game involves cognitive and psychomotor skills that go hand in hand with concentration and questions about Islamic Religious Education learning materials. Students are asked to participate in the game of snakes and ladders and answer questions given by the teacher based on the flow of the game. Efforts to strengthen the subject of Islamic Religious Education with the game-based learning method using Islamic smart snakes and ladders are proven to be able to create a happy atmosphere for students, so that they are enthusiastic about participating in the learning process actively and responsively.